2021
DOI: 10.1055/s-0041-1723812
|View full text |Cite
|
Sign up to set email alerts
|

The Transformation of Intracranial Subdural Hygroma to Chronic Subdural Hematoma Following Endoscopic Spinal Surgery: A Case Report

Abstract: Background We present the case of an intracranial subdural hygroma resulting from intraoperatively undetected dural tear after unilateral biportal endoscopic (UBE) spine surgery for lumbar spinal stenosis. Case Description An 80-year-old woman presented with insidious onset, gradually progressing low back pain, and right leg pain of 1-year duration. The pain radiated to the right L4–L5 dermatomes. Neurogenic intermittent claudication was <300 m. Motor function was normal. Lumbar magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The main source of hemorrhage of the CSDH is the outer membrane of the CSDH, which is fed from the dural vasculature [ 18 ]. The inner membrane of the CSDH has less vascularity due to the low reaction potential of the adjacent arachnoid membrane [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main source of hemorrhage of the CSDH is the outer membrane of the CSDH, which is fed from the dural vasculature [ 18 ]. The inner membrane of the CSDH has less vascularity due to the low reaction potential of the adjacent arachnoid membrane [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subdural hygromas are frequently associated with spontaneous intracranial hypotension[ 18 ]. Lin et al [ 19 ] described a case of intracranial subdural hygroma after endoscopic lumbar spinal surgery. A retrospective review from 2008 to 2013 of 1113 consecutive patients who underwent spinal surgery found 4 patients (0.27%) with intracranial hygromas[ 20 ].…”
Section: Discussionmentioning
confidence: 99%